Investigation into Discrepancies in Alignment and Levelling of Precast Segmental Box Girders (SBGs) During Launching for LRT 3, from Bandar Utama to Johan Setia (Package GS10) - Mohd Idris, Nurul Afiqah; Ganasan, Reventheran; Ismail, Akmal Hakim; Omran, Mustapha Kamil; Ngadiron, Zuraidah; Nayaka, Ramesh; Hosen, Md Akter (Journal of Advanced Industrial Technology and Application, 2024)
In recent decades, there has been a notable global increase in the utilization of precast concrete segmental bridges within construction projects. However, discrepancies have been observed in the height of precast Segmental Box Girders (SBGs) installed alongside PS1 (monolithic), deviating from project specifications. This discrepancy impacts the deck level and consequently influences the Top of Rail (TOR). Consequently, a study was undertaken at AlKauthar Kinematics Sdn Bhd, a company involved in the LRT3 project’s construction, with a specific focus on the casting and installation of Segmental Box Girders. The study’s objectives include identifying the factors contributing to precast SBG misalignment during the LRT3 project’s launch at P25-08, analyzing data for realignment purposes, and proposing design methodologies for manufacturing SBGs. The methodology employed in this study entails the analysis of data sourced from the industry, utilizing As-Built Surveys conducted by surveyors. Findings indicate that precast SBG misalignment during launching at P25-08 is primarily attributed to on-site errors, particularly casting errors during the construction of the cast-in-situ monolithic segment P25-08. This insight is invaluable for both governmental bodies and private construction organizations in mitigating project setbacks.